2021
DOI: 10.1002/bies.202000343
|View full text |Cite
|
Sign up to set email alerts
|

The tree of life describes a tripartite cellular world

Abstract: The canonical view of a 3-domain (3D) tree of life was recently challenged by the discovery of Asgardarchaeota encoding eukaryote signature proteins (ESPs), which were treated as missing links of a 2-domain (2D) tree. Here we revisit the debate. We discuss methodological limitations of building trees with alignment-dependent approaches, which often fail to satisfactorily address the problem of ''gaps.'' In addition, most phylogenies are reconstructed unrooted, neglecting the power of direct rooting methods.Ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 85 publications
(185 reference statements)
0
6
0
Order By: Relevance
“…In the case of actin, the proto‐eukaryotic HGT hypothesis is strongly supported by phylogenetic analyses showing that the various forms of actins present in Asgards branch between the various clades of eukaryotic actin paralogs (cytoplasmic actin and ARPs) that were already present in LECA 43,44 . Also, corroborating this hypothesis, Nasir et al 7 concluded from a comparative analysis of conserved folds that ESPs are of relatively recent origin and could correspond to late HGTs between Archaea and Eukarya.…”
Section: Hgt Between Asgards and Proto‐eukaryotes Could Explain The P...mentioning
confidence: 83%
See 4 more Smart Citations
“…In the case of actin, the proto‐eukaryotic HGT hypothesis is strongly supported by phylogenetic analyses showing that the various forms of actins present in Asgards branch between the various clades of eukaryotic actin paralogs (cytoplasmic actin and ARPs) that were already present in LECA 43,44 . Also, corroborating this hypothesis, Nasir et al 7 concluded from a comparative analysis of conserved folds that ESPs are of relatively recent origin and could correspond to late HGTs between Archaea and Eukarya.…”
Section: Hgt Between Asgards and Proto‐eukaryotes Could Explain The P...mentioning
confidence: 83%
“…The discovery of Asgards thus did not reduce the formidable divide existing between the archaeal and eukaryotic phenotypes. The transformation of an archaeon into a eukaryote still involves many transitions that have never been observed in nature 7,[60][61][62] . As pointed out by Nasir et al 7 , all known organisms forming intimate endosymbiotic or ectosymbiotic associations have maintained their domain identity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations